1959
DOI: 10.1149/1.2427437
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of the Flade Potential

Abstract: Previous explanations of the Flade potential have been reviewed critically. A new explanation based on a single phase passive film of γ‐Fe2O3 having non‐ uniform defect concentration and type is advanced. The potential determining reaction is considered to be that between excess oxygen in the outer p‐type layers and hydrogen ions and electrons. The inner n‐type oxide is destroyed by reductive dissolution in acid media and by exchange of oxygen ions with hydroxyl ions in solution having pH values higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1961
1961
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
(54 reference statements)
2
28
0
Order By: Relevance
“…[7]. Accordingly the passivation potential observed in neutral borate solutions can be interpreted as corresponding to the equilibrium potential for the reaction between ~,-Fe203 and Fe + + ion in solution.…”
Section: Significance Of the Passivation Potentialmentioning
confidence: 99%
“…[7]. Accordingly the passivation potential observed in neutral borate solutions can be interpreted as corresponding to the equilibrium potential for the reaction between ~,-Fe203 and Fe + + ion in solution.…”
Section: Significance Of the Passivation Potentialmentioning
confidence: 99%
“…The authors proposed the existence of a higher valence state of Fe in the outer region of the passive film to account for this observation. Pryor (28) proposed earlier the existence of a gradation in defect concentration throughout a single-phase y-Fe 2 0 3 passive film with the passive oxide near the oxide-metal interface containing excess cations (metal excess, n type) and with the passive oxide near the oxide-solution interface containing excess oxygen ions (metal deficient, p type). Electrical neutrality is provided by the existence of the appropriate number of negative holes near the oxide-metal interface and positive holes near the oxide-solution interface.…”
Section: Mechanism Of Passivationmentioning
confidence: 99%
“…Dielectric measurements and polarization studies (74) show that electrical neutrality in the oxide is restored by the reaction A1(Lr + 30fL) + 3CI(s) + 3H(~) = 3Clii) + AIM + 30H(s) (28) where the subscript (L) refers to the lattice and (S) to the solution. Accordingly, the three-electron deficiency resulting from three CI--0 2 -exchanges is compensated by one aluminum ion passing into solution.…”
Section: Pitting In the Active Potential Rangementioning
confidence: 99%
“…On the basis of the values of E pp (1,220 mV), some investigators have reported that the protective layer probably corresponds to a nonstoichometric higher oxide of iron. [8][9] However, it was difficult to ascertain the nature and composition of the film on the basis of results of the present investigation (E pp = 420 mV to 750 mV).…”
Section: Corrosion Science Sectionmentioning
confidence: 73%